Photocatalytic conversion of carbon dioxide: From products to design the catalysts. (December 2019) - Fu, Zhiyan; Yang, Qi; Liu, Zhan; Chen, Fei; Yao, Fubing; Xie, Ting; Zhong, Yu; Wang, Dongbo; Li, Jing; Li, Xiaoming; Zeng, Guangming
Highlights: The reduction of CO2 to produce the renewable fuels or valuable chemicals. The main reduction products are discussed and a more superior catalyst is selected from the viewpoint of the product. A common strategy for converting CO2 to the desired target product. Abstract: The emissions of carbon dioxide (CO2 ) from the combustion of hydrocarbon fuels have brought increasingly serious global warming. Photocatalytic conversion of CO2 to the renewable fuels or valuable chemicals is proposed as an effective solution to simultaneously achieve the reduction of CO2 emission, the use of sustainable solar energy and the harvest of products with high added-value. Various products such as methane (CH4 ), methanol (CH3 OH), carbon monoxide (CO) have been gained through the photocatalytic conversion of CO2 . This review systematically summarized the research progress of photocatalytic conversion of CO2 from the product selectivity point of view. Particularly, the common strategies to covert CO2 into the desired target products, including the surface modification of catalyst, the control of reaction conditions, the selection of incident light source, are completely discusses. Finally, the challenges and prospects in achieving efficient, stable and selective CO2 photoconversion are pointed out.